Financial Accounting - Libby Patricia; Libby Robert; Short Daniel G (Mcgraw Hill Irwin, 2001)
Financial Statements and Business Decisions, Investing and Financing Decisions and the Balance Sheet, Operating Decisions and the Income Statement, The Adjustment Process and Financial Statements, Communicating and Interpreting Accounting Information, Reporting and Interpreting Accounting Information, Reporting and Interpreting Sales Revenue and Receivables and Cash, Reporting and Interpreting Cost of Goods Sold and Inventory, Reporting and Interpreting Property and Plant and Equipment; Natural Resources; and Intangibles, Reporting and Interpreting Liabilities, Reporting and Interpreting Bonds, Reporting and Interpreting Owners' Equity, Reporting and Interpreting Investments in Other Corporations, Statement of Cash Flows, Analyzing Financial Statements, Present and Future Value Tables, Ammerican Eagle Outfitters Annual Report, Urban Outfitters Annual Report, Standard and Poor's Industry Ratio Report, The Formal Recordkeeping System, Glossary, Illustration Credits, Index.